Lipid Profile of the Freshwater Pearl Mussel Margaritifera margaritifera Inhabiting Different Biotopes of the Lake-River System of the Kem River, White Sea Basin - Svetlana N. Pekkoeva; Viktor P. Voronin; Evgeny P. Ieshko; Natalia N. Fokina; Denis A. Efremov; Svetlana A. Murzina (Diversity, 2023)
The freshwater pearl mussel Margaritifera margaritifera is considered to be the most rapidly declining species of freshwater bivalve, whereas its colonies in rivers of the White Sea Basin remain the most numerous in the world. The lipid profiles of mantle, muscle (foot), and digestive gland tissues of the freshwater pearl mussel from the Kem, Ukhta, and Vozhma Rivers in autumn (end of September, early October) were studied using high performance thin-layer chromatography. The highest total lipid [TL] content was found in the digestive gland. Cholesterol esters, non-esterified fatty acids, phospholipids, and cholesterol were the dominant lipids in all studied tissues. The reduced triacylglycerol content in the mussels was associated with its utilization during the spawning period. The colony of the freshwater pearl mussel inhabiting the Vozhma River was distinguished by higher TL content in the mantle and digestive gland. Data on the size-age characteristics of mollusks from the Kem, Ukhta, and Vozhma Rivers and the relationship between the structural and storage lipid content and size-age parameters are discussed. The results are important for different conservation strategies of endangered species, such as the freshwater pearl mussel, especially in ecological monitoring based on evaluation of the physiological and biochemical state of mollusks and rare natural colonies.